Development of Acute Retinal Necrosis in a Patient with Ocular Sarcoidosis: A Case Report. (3rd October 2019) - Takayama, Kei; Kaburaki, Toshikatsu; Takeuchi, Masaru
ABSTRACT: Purpose : To report a case of acute retinal necrosis (ARN) caused by varicella-zoster virus (VZV) in an elderly patient with ocular sarcoidosis after oral corticosteroid indication. Methods : Retrospective case report. Results : A 75-year-old male with a past history of ocular sarcoidosis came with blurred left vision. Ocular findings in the left eye were consistent with ocular sarcoidosis, while no inflammation in the right eye. On day 14, intraocular inflammation in the left eye resolved by topical corticosteroid, but inflammatory cells were found in the right eye. Suspecting recurrence of ocular sarcoidosis, systemic corticosteroid was initiated. On day 21, inflammation worsened, and the presence of extended yellowish white peripheral retinal lesion in the right eye suggested ARN. Polymerase chain reaction (PCR) testing using ocular fluid detected 3.0 × 107 copies/ml of VZV DNA. Conclusions : In the case of poor response to immunosuppressive therapy in elderly uveitis, infection including ARN should be considered. Immediate PCR testing for pathogen screening is required.